Schisandrin C enhances type I IFN response activation to reduce tumor growth and sensitize chemotherapy through antitumor immunity - Yang, Huijie; Zhan, Xiaoyan; Zhao, Jia; Shi, Wei; Liu, Tingting; Wei, Ziying; Li, Hui; Hou, Xiaorong; Mu, Wenqing; Chen, Yuanyuan; Zheng, Congyang; Wang, Zhongxia; et al. (Frontiers in Pharmacology, 2024)
With the advancing comprehension of immunology, an increasing number of immunotherapies are being explored and implemented in the field of cancer treatment. The cGAS-STING pathway, a crucial element of the innate immune response, has been identified as pivotal in cancer immunotherapy. We evaluated the antitumor effects of Schisandra chinensis lignan component Schisandrin C (SC) in 4T1 and MC38 tumor-bearing mice, and studied the enhancing effects of SC on the cGAS-STING pathway and antitumor immunity through RNA sequencing, qPCR, and flow cytometry. Our findings revealed that SC significantly inhibited tumor growth in models of both breast and colon cancer. This suppression of tumor growth was attributed to the activation of type I IFN response and the augmented presence of T cells and NK cells within the tumor. Additionally, SC markedly promoted the cGAS-STING pathway activation induced by cisplatin. In comparison to cisplatin monotherapy, the combined treatment of SC and cisplatin exhibited a greater inhibitory effect on tumor growth. The amplified chemotherapeutic efficacy was associated with an enhanced type I IFN response and strengthened antitumor immunity. SC was shown to reduce tumor growth and increase chemotherapy sensitivity by enhancing the type I IFN response activation and boosting antitumor immunity, which enriched the research into the antitumor immunity of Schisandra chinensis and laid a theoretical basis for its application in combating breast and colon cancer.